Міжнародно-правові стандарти правового регулювання працевлаштування молоді. - Трюхан, Оксана Анатоліївна; Трюхан, Оксана Анатольевна; Triukhan, О (My University, 2011)
This article is devoted to the research of the peculiarities of the legal regu- lation of the youth work. The paper analyzes the international legal acts and some labor laws of Ukraine. The paper deals with the right of young people to work in the system of human rights and freedoms. Peculiarities of the legal regulation of the working conditions of the young workers are also studied
Трюхан О. А. Міжнародно-правові стандарти правового регулювання працевлаштування молоді / О. А. Трюхан // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 89-96.
Keywords: Працевлаштування молоді; Міжнародно-правові стандарти; Трудоустройство молодёжи; Международно-правовые стандарты; youth employment; International legal standards